BASIC PROVISIONS FOR FORMING TOOLS FOR MANAGEMENT OF ECONOMIC DEVELOPMENT OF TERRITORIAL COMMUNITIES - AVHUSTYN, Ruslan; DEMKIV, Iryna; STRUMETSKYI, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The formation of an effective system for managing the socio-economic development of territorial communities is achievable only if a stable balance is established between the powers of state authorities and self-government structures of territorial communities. Such a balance implies an optimal distribution of management functions at the local level, based on a combination of two key factors - autonomy in decision-making and responsibility for their consequences, including criminal liability in cases of illegal or opportunistic decisions. In conditions of deep crisis, the primary task for territorial communities is not only an emergency response to challenges, but also strategic planning for the recovery and further development of the local economy. In particular, the need to implement effective economic development management tools is becoming more urgent. Such tools include: creating a favorable investment climate, providing support to small and medium-sized businesses, creating an institutional framework for the integration of relocated businesses, and developing partnerships between all stakeholders at the local level. Assessment of the effectiveness of territorial communities in the war and post-war periods should be based on a number of critical indicatorsAmong them are ensuring the functioning of social infrastructure, the availability of quality social services for the local population, supporting economic activity and entrepreneurship, developing inclusive communication channels between authorities, business and the public, as well as the successful integration of new residents and business entities into the economic environment of the community.Achieving an optimal model of managing the economic development of territorial communities is possible only if their competencies are expanded, in particular by delegating additional managerial powers to them.
Keywords: territorial communities; management of economic development of territorial communities; measures of management of territorial communities